2014
DOI: 10.1002/chem.201402875
|View full text |Cite
|
Sign up to set email alerts
|

Zincocene and Dizincocene N‐Heterocyclic Carbene Complexes and Catalytic Hydrogenation of Imines and Ketones

Abstract: The N-heterocyclic carbene (NHC) adducts Zn(Cp(R))(2) (NHC)] (Cp(R) =C(5)HMe(4), C(5)H(4) SiMe(3); NHC=ItBu, IDipp (Dipp=2,6-diisopropylphenyl), IMes (Mes=mesityl), SIMes) were prepared and shown to be active catalysts for the hydrogenation of imines, whereas decamethylzincocene [ZnCp*(2)] is highly active for the hydrogenation of ketones in the presence of noncoordinating NHCs. The abnormal carbene complex [Zn(OCHPh(2))(2) (aItBu)](2) was formed from spontaneous rearrangement of the ItBu ligand during incompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 92 publications
(66 reference statements)
1
17
0
Order By: Relevance
“…While several main group metals exhibit activity for imine hydrogenation, homogeneous ketone hydrogenation by main group metals is exceptionally limited. The reported examples involve extremely high pressures, 58 , 60 , 61 the use of additives, 62 or a narrow substrate scope. 58 , 60 , 63 Thus, it is significant that we found that 1 can catalyze the hydrogenation of ketones with aromatic, aliphatic, and mixed aromatic/aliphatic R and R′ substituents under 65 bar of H 2 at 140 °C.…”
Section: Resultsmentioning
confidence: 99%
“…While several main group metals exhibit activity for imine hydrogenation, homogeneous ketone hydrogenation by main group metals is exceptionally limited. The reported examples involve extremely high pressures, 58 , 60 , 61 the use of additives, 62 or a narrow substrate scope. 58 , 60 , 63 Thus, it is significant that we found that 1 can catalyze the hydrogenation of ketones with aromatic, aliphatic, and mixed aromatic/aliphatic R and R′ substituents under 65 bar of H 2 at 140 °C.…”
Section: Resultsmentioning
confidence: 99%
“…16 The dialkoxide adducts [(IDipp)Zn(OCHR 2 ) 2 ] (25, R = Ph, t-Bu) were produced by hydrogenation of [ZnCp* 2 ] (4 bar H 2 ) in the presence of R 2 C=O and IDipp. 33 Alternatively, protonolysis of [ZnCp* 2 ] with R 2 CHOH (R = Ph, t-Bu; 2 equiv) and subsequent addition of IDipp also allowed the…”
Section: Scheme 15 Co 2 Hydrosilylation Catalysis Mediated By Zn-h Camentioning
confidence: 99%
“…The aluminium hydride compound (iso-butyl) 2 AlH is an odd example of a main group metal catalyst that can be used, but needs harsh conditions (100 bar H 2 , 100 °C, 24 h) 27 . Recently, a zinc hydride catalyst was introduced but similarly high pressures need to be applied (70-100 bar) 28,29 . Figure 2b shows metal-free organocatalysts.…”
mentioning
confidence: 99%